Of mammoths and other monsters: historic approaches to the submerged Palaeolithic. (19th July 2016) - Bynoe, Rachel; Dix, Justin K.; Sturt, Fraser
Abstract: Abstract : Recent research on the submerged central and southern North Sea basin has focused on the end of the story: the last few millennia before the final inundation. Much older deposits do survive, however, and are documented by collections of Pleistocene fauna recovered by fishing fleets operating from Dutch and British ports during the nineteenth and early twentieth centuries. Analysis of the British collections allows them to be assigned to specific areas of seabed and to broad stages of the Pleistocene climatic sequence. The results provide evidence of more complex and fragmentary undersea landscapes than can be detected using geophysical approaches alone, and indicate targeted areas for future work.